STRATEGI PENGEMBANGAN USAHA MIKRO MILIK MAHASISWA - Imron Rosyadi (Benefit: Jurnal Manajemen dan Bisnis, 2013)
The purpose of this research is  arrange a strategy model for developing micro and small enterprises owned by the student on the Colleges strategic role-based. Research conducted in the selected region: Surakarta, Sukoharjo, Klaten and Boyolali Regency. The data used is primary and  secondary data. Primary  data  is  obtained  using  the  techniques of observation,  focus group discussion (FGD) and in-depth interview on micro and small entrepreneur’s students in the area of  research, the secondary data is obtained  from various publication sources. Analytical method used is descriptive-analytic approach. This result  showed  that: (1) micro and small enterprises owned by  student face various problems especially capital aspect, enterprises  management and  entrepreneurship skills; (2) the problems that have been identified is used a basis of arrangement a SWOT analysis from formulating a grand strategy and model development of micro and small enterprises (Figure  4.3);  (3) The  strategic  role  of  the  Colleges  in  developing  micro  and  small enterprise:  (a)  formulating  strategic for the developing  of  small and micro enterprises through: (i) the teaching of entrepreneurship and enterprises management soft skills-based and (ii) conducting education and training an intensive, systematic and integrated about enterprises management and entrepreneurship science and technology-based; (b) colleges synergize  with  Banks  and  HPMI  for  purposes  related  to  the  evaluation  of  the feasibility business  plan,  flanking  business  and  business  consultant for entrepreneurs students; (c) providing  ease  of  access to capital for  entrepreneurs  students his business plan is considered feasible by a team of assessment.